“Imposter-Children” in the UK Refugee Status Determination Process - Silverman, Stephanie J. (Refuge: Canada’s Journal on Refugees, 2016)
This article describes and analyzes an emerging problematic in the asylum and immigration debate, which I cynically dub the “imposter-child” phenomenon. My preliminary exploration maps how the imposter-child relates to and potentially influences the politics and practices of refuge status determination in the United Kingdom. I argue that the “imposter-child” is being discursively constructed in order to justify popular and official suspicion of spontaneously arriving child asylum-seekers in favour of resettling refugees from camps abroad. I also draw connections between the discursive creation of “imposter-children” and the diminishment of welfare safeguarding for young people. Further complicating this situation is a variety of sociocultural factors in both Afghanistan and the United Kingdom, including the adversarial UK refugee status determination process, uncertainty around how the United Kingdom can“prove” an age, and a form of “triple discrimination” experienced by Afghan male youth. Through unearthing why the “imposter-child” is problematic, I also query why it is normatively accepted that non-citizens no longer deserve protection from the harshest enforcement once they “age out” of minor status.